Sustainable Nixtamalization of Wheat Bran by Microwave Processing and Eggshell-Derived Calcium Citrate - Argun, Mustafa Samil; Saricoban, Cemalettin; Aslan, Mine; Ertas, Nilgun; Atalar, Ilyas; Kurt, Abdullah (WILEY, 2026)
This study evaluated a sustainable nixtamalization strategy for wheat bran using microwave processing and eggshell-derived calcium citrate as an alternative to CaCl2. Wheat bran was nixtamalized with CaCl2 or eggshell-derived calcium citrate under microwave-assisted conditions (6, 9, or 12 min) or conventional boiling, followed by steeping, washing, drying, and incorporation into bread at 15% (w/w). Bran and bread samples were analyzed for chemical composition, phytic acid content, mineral profile, ATR-FTIR characteristics, bread technological and textural properties, and in vitro mineral digestion. Nixtamalization increased Ca enrichment in bran and breads and improved loaf volume, specific volume, and moisture retention compared with untreated bran bread, with eggshell-derived calcium citrate performing comparably to CaCl2. Short-to-moderate microwave processing preserved the structural integrity of bran and bread matrices, whereas prolonged microwave treatment (12 min) caused spectral distortion in polysaccharide-related FTIR regions and deterioration of bread volume and texture, regardless of calcium source. Nutritionally, nixtamalization enhanced in vitro Ca digestion, mainly governed by Ca concentration in the bread matrix, while in vitro Fe digestion remained limited and phytic acid did not exert a dominant inhibitory effect. Eggshell-derived calcium citrate can replace conventional calcium salts when combined with controlled microwave processing.
Keywords: eggshell calcium citrate; microwave processing; phytate; wheat bran; BREAD; COOKING; Engineering; Food Science & Technology